Desempenho de diferentes indicadores de obesidade na identificação da resistência à insulina em participantes do Estudo Longitudinal de Saúde do Adulto (ELSA Brasil) - Santos, Hully Cantão dos (2021)
This is a master's thesis whose objective was to evaluate the performance of different IO in identifying IR. The dissertation was divided into two articles: a systematic review article and an original article using data from the Longitudinal Study of Adult Health (ELSA-Brasil). The review article evaluated the association between OI and IR through search strategies in Medline, Pubmed, LILACS, IBECS-ES and MedCarib databases until April 2019. Twelve articles were included and a positive association was observed between the indicator of obesity and HOMAIR in all studies. The obesity indicator that was most positively associated with HOMA-IR was BMI, followed by waist circumference. The second article aimed to analyze the cutoff points of different obesity indicators to identify the presence of IR calculated by HOMA-IR in men and women of different race/color groups. The sample consisted of 12,257 participants. The performance of the Body Mass Index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) were evaluated. IR was assessed using the HOMA-IR index, considering values above P75 as an outcome. The association between IO and HOMA-IR was analyzed using logistic regression. The optimal cutoff points were determined by maximizing the Youden index from the Receiver Operating Characteristic (ROC) curves. There was a positive association between OI and IR. The three IOs showed similar performance. The obesity indicator that showed the greatest difference in cutoff values between genders was WC (men: 96.4 cm; women: 87.9 cm). Although WC had a slightly higher performance, it is recommended to use the BMI with a cutoff value of 27.0 kg/m² for men and women, regardless of ethnicity, to predict IR in primary care, since its performance was similar to CC and simple measures are needed to obtain it. The findings of both studies demonstrated that the BMI can be used in the screening of IR in a satisfactory way and can be used as a preventive strategy for the development of DM2 and cardiovascular diseases.